Wild cowboy ways - Brown, Carolyn, 1948- (Brown, Carolyn, 1948- Lucky Penny Ranch novel., 2015)
Allie Logan isn't the type to land a hot hunk of cowboy. Truth is, she's given up on dating since shedding her no-good ex. But the new owner of the most ramshackle ranch in Texas might just change her mind about that. He's six-foot-plus of tall, dark, and charming-the kind of guy who could make a girl throw caution to the wind . . . or the kind of guy who could break her heart. Blake Dawson hopes he can make Lucky Penny Ranch finally live up to its name, but the property needs a ton of work. Allie and her carpentry skills are his best shot at getting things in order. Besides the fact that her brown eyes and dangerous curves have him roped and tied. Now Blake only needs to convince her that a wild cowboy can be tamed by love-and she's just the one to do it . . .